TERRORISM AND RELIGIOUS VIOLENT EXTREMISM IN PAKISTAN - Syed Noor Ul Hassan Hashmi; Asghar Ullah Khan; Syed Mahmood Ul Hassan Hashimi; Hani Fatima; Zain Ul Abiden Malik; Azkia Hashimi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Pakistan has been subjected to a number of terrorist-related violent threats and incidents since September 11, 2001. People’s social, economic, and psychological well-being has been jeopardized by a never-ending and intermittent wave of terrorist attacks.Terrorism entails the intentional infliction of violence or force on a specific population in order to instill fear in order to achieve desired religious, psychological, or political objectives. As a result, terrorism causes harm to people’s physical, economic, psychological, and emotional well-being..In fact, the fear of terrorism has decreased to a large extent as a result of counter-terrorism measures implemented around the world, especially in Pakistan, which ranks fifth in the terrorism index in 2018.Human behavior and responses to terrorism, as well as perceptions of fear and the risks of terrorism and abuse, can be shaped by the media.It is attributed to a variety of perceptions of exposure to violence as a result of violent attacks that may or may not be specifically linked to acts of terrorism.The levels of fear crime and terrorism in Pakistan are determined by all of these various forms of crimes, social circumstances, and personal experiences.